Kantian Notions of Feminine Beauty and Masculine Sublimity in Hawthorne’s ‘The Birthmark’ - Hafezi, Najmeh; Ahmadian, Moussa; Amjad, Fazel Asadi (Mediterranean Journal of Social Sciences, 2012)
Hawthorne’s ‘The Birthmark’ is one of his short stories whose theme falls among the domain of experimenting humannature in the fields of art, religion, and science. Regardless of the birthmark itself which represents the Original Sin, a conflictbetween masculine attitude and feminine perspective toward perfection and beauty is artfully manifested in this story. The paperstudy employs the notions of the beautiful and the sublime according to Immanuel Kant’s Observations on the Feeling of theBeautiful and Sublime in which he puts forward the idea that different sexes possess different perceptions of events andenvironment. From his viewpoint, women are mostly capable to feel the beautiful and sympathy, while men, with their tendencyto perfection, possess and convey the feeling of the sublime. Several events, disputes and descriptions in ‘The Birthmark’,clearly exemplify women’s zeal for beauty and men’s seeking the perfection. Hawthorne proves that oversensitivity to perfectionand sublimity can be a destructive force for the beautiful. One should not defy nature to reconcile his or her internal desires.Within the quest to win perfection by means of limited power of science, the only winner is true love.